Experimental Measurements of Wax Precipitation Using a Modified Method of Simultaneous Centrifugation and High-Temperature Gas Chromatography - Huishu Liu (MDPI AG, 2021)
Wax precipitation and deposition are serious flow assurance problems. Wax precipitation is investigated simultaneously using centrifugation and high-temperature gas chromatography (C-HTGC) to obtain the amount and component distribution of precipitated wax in artificial waxy oil and diesel at different temperatures. However, the conventional C-HTGC method gives upper measurements of the amount of precipitated wax, as it ignores wax dissolved in crude oil in the centrifugal cake. A modified C-HTGC method was developed to obtain the precipitated solid fraction of crude oil, based on the mass balances of the non-crystallized fraction of the centrifuged cake. The weight, percent and carbon number distribution of precipitated solid wax crystals at different temperatures of artificial oil and 0# diesel were obtained. It was found that wax precipitation characteristics are affected by many factors, including the carbon number distribution of the oil, the sensitivity of alkane crystallization to temperature and the temperature of the waxy oil solution. The average carbon number of alkanes in precipitated wax crystals decreases with the decrease in temperature. The distribution of alkanes in solid wax crystals is roughly the same as that in 0# diesel but slightly heavier than in diesel. Alkanes with high carbon numbers precipitate simultaneously with those with low carbon numbers.